High-efficient crystallization promotion and melt reinforcement effect of diblock PDLA-b-PLLA copolymer on PLLA. (9th January 2020) - Yan, Cong; Jiang, Yuan-Ping; Hou, De-Fa; Yang, Wei; Yang, Ming-Bo
Abstract: In this work, a diblock PDLA-b-PLLA copolymer (BCP) was synthesized and employed to modify commercial poly l -lactide (PLLA) subsequently. The morphology and performance of BCP/PLLA blends were investigated using the traditional poly d -lactide (PDLA)/PLLA blends as controls. The morphology of BCP/PLLA is more uniform than that of PDLA/PLLA, demonstrating the compatibility and interaction between stereocomplex (SC) crystals and PLLA matrix are optimized by the PLLA blocks in BCP. Under the same amount of PDLA (5 wt%), BCP/PLLA shows dramatically improved crystallization behavior and rheological properties compared with PDLA/PLLA. Especially the maximum relaxation time of the optimal BCP/PLLA is markedly extended to 39.24 s (which is 0.018 s for pure PLLA). These results reveal that the PLLA blocks in BCP play a significant role in the superior performance of BCP/PLLA. Therefore, this work may have important meaning for designing high-efficient modifiers of PLA. Graphical abstract: Image 1 Highlights: A diblock PDLA-b-PLLA copolymer (BCP) is synthesized to modify the PLLA matrix. The compatibility and interaction between SC crystals and PLLA matrix are optimized by the PLLA blocks in BCP. BCP/PLLA blends show dramatically improved crystallization behavior and rheological properties. The mechanism of BCP efficiently modifying PLLA is revealed.